Career satisfaction and resilience among Oklahoma band directors. - Howard, Scott Eugene. (My University, 2006)
The purpose of this study was to investigate the demographic, professional, social, and personal influences related to career satisfaction and teacher resilience among instrumental music educators, as determined by responses from an anonymous Instrumental Music Director Survey (IMDS). Instrumental music directors (N = 214) currently associated with the Oklahoma Secondary Schools Activities Association (O.S.S.A.A.) participated in an on-line survey consisting of two sections. The first section collected biographical information and the latter was comprised of questions inquiring about career satisfaction and teacher resilience. Data were analyzed and coded according to subjects' responses. The data indicated that directors were satisfied with their positions (n = 126, 59%) and felt they were properly trained by their pre-service institutions (n = 156, 73%). Most directors indicated they would return for another school term (n = 176, 82%). A multiple linear regression was used to determine that seven variables (pre-service training, time management skills, budget, choose teaching again as a profession, salary, colleague and peer support) were all significant factors ( p < .05) related to career satisfaction. Finally, a discriminant analysis indicated that social support structures (i.e. colleagues, students, parents, administrators, and the community) were all significant factors ( p < .05) of teacher retention.
Keywords: Music teachers Oklahoma.; Music teachers Job satisfaction.; Education, Administration.; Psychology, Industrial.; Job satisfaction Oklahoma.; Education, Music.; Band directors Oklahoma.; Band directors Job satisfaction.